1997
DOI: 10.1111/1467-8489.00005
|View full text |Cite
|
Sign up to set email alerts
|

Crop genetic resource policy: the role of ex situ genebanks

Abstract: The world-wide capacity of genebanks for ex situ conservation of crop genetic resources has increased greatly since the 1970s, improving the access of crop breeders to landraces and wild and weedy relatives. But utilization of genebank resources has not kept pace. The set of popular cultivars in major crops is typically rather small, and their ancestry encompasses only a fraction of the genetic diversity currently available in other cultivars. Discussions of farmers' rights that focus on compensation for curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Thus, a sizeable volume of material has been used in a breeding program, found worthy of further investigation, or has been useful in other ways. While certain materials may never be used, the number of samples estimated to be in use seemed to counter past assertions that the material in a genebank is rarely used (see Wright, 1997, andWidrlechner andBurke, 2003, for differing assessments).…”
Section: Estimates Of Germplasm Utilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, a sizeable volume of material has been used in a breeding program, found worthy of further investigation, or has been useful in other ways. While certain materials may never be used, the number of samples estimated to be in use seemed to counter past assertions that the material in a genebank is rarely used (see Wright, 1997, andWidrlechner andBurke, 2003, for differing assessments).…”
Section: Estimates Of Germplasm Utilitymentioning
confidence: 97%
“…Still, Widrlechner and Burke's (2003) analysis of distributions within selected NPGS collections found that "Contrary to commonly held views… many accessions are distributed frequently and few languish unrequested." However, some economists have asserted that the materials in genebanks are rarely used (Wright, 1997). This has led others to find that their worth is low ("negligible," in the words of Simpson and Sedjo, 1998).…”
Section: Economic Value Of Plant Genetic Resources Conserved In Genebmentioning
confidence: 99%
“…The use of available genetic resources in crop improvement is the most neglected part of germplasm conservation (de Wet, 1989). A very large gap exists between actual utilization of the germplasm and availability of collection in the genebanks (Wright, 1997;Upadhyaya et al, 2006). Germplasm resources would not be used if the information needed by crop improvement scientists is not readily available.…”
Section: Limitations In Germplasm Usementioning
confidence: 99%
“…In spite of its multiple uses, pigeonpea germplasm has been used primarily for developing high grain yielding varieties of different maturity groups, as sources of resistance to major diseases and insect pests and for other simply inherited traits. Some economists have asserted that the materials in genebanks are rarely used (Wright, 1997). Usually the number of useful germplasm accessions for breeding is less than 5% and mostly less than 1% (Goodman, 1990) The prime reasons for the low use of diverse germplasm for improvement of quantitative traits in the plant breeding programs are the extended time and high costs involved in identifying these useful accessions.…”
mentioning
confidence: 99%